2015
DOI: 10.1039/c5sm01348h
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected coupling between flow and adsorption in porous media

Abstract: We study the interplay between transport and adsorption in porous systems under a fluid flow, based on a lattice Boltzmann scheme extended to account for adsorption. We performed simulations on well-controlled geometries with slit and grooved pores, investigating the influence of adsorption and flow on dispersion coefficient and adsorbed density. In particular, we present a counterintuitive effect where fluid flow induces heterogeneity in the adsorbate, displacing the adsorption equilibrium towards downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
(71 reference statements)
3
32
0
Order By: Relevance
“…Thus, a dead volume exits in the material, and not all adsorption sites are active in these given conditions. This result parallels what we have seen in earlier work, 6 in which we studied the velocity profile for fluid flow in crenelated pore systems and showed the existence of "dead volume", i.e. a non negligible part of the crenel where the velocity of the fluid is close to zero.…”
Section: Crenelated Poresupporting
confidence: 91%
“…Thus, a dead volume exits in the material, and not all adsorption sites are active in these given conditions. This result parallels what we have seen in earlier work, 6 in which we studied the velocity profile for fluid flow in crenelated pore systems and showed the existence of "dead volume", i.e. a non negligible part of the crenel where the velocity of the fluid is close to zero.…”
Section: Crenelated Poresupporting
confidence: 91%
“…For example, various slip models have been used to describe the slippage effect on the pore walls [20][21][22][23]. In addition to the non-classical flow behaviors, prior research also indicated that the Knudsen diffusion can dominate the transport process in nanopores when the Knudsen number is large because the collisions between gas molecules and pore wall are more frequent than collisions between gas molecules [24][25][26][27][28]. These insights are highly relevant to the gas transport in shale gas formations.…”
Section: Introductionmentioning
confidence: 99%
“…Several descriptions and extensions of this method have since been proposed for various applications, see e.g. [33,35,36,[43][44][45][46]. In the present work, we show that this method can be used for charged mobile (hence experiencing diffusion, advection and migration) and adsorbing/desorbing species -a combination of features which had to date not been investigated previously despite its relevance in the many contexts described in the introduction.…”
Section: Moment Propagationmentioning
confidence: 60%